2008
DOI: 10.1016/j.neuroscience.2008.08.051
|View full text |Cite
|
Sign up to set email alerts
|

α2-Noradrenergic antagonist administration into the central nucleus of the amygdala blocks stress-induced hypoalgesia in awake behaving rats

Abstract: Stress-induced hypoalgesia (SIH) is an adaptive behavioral phenomenon mediated in part by the amygdala. Acute stress increases amygdalar noradrenaline levels and focal application of α 2 -adrenoceptor agonists in the central nucleus of the amygdala (CeA) is antinociceptive. We hypothesized that α 2 -adrenoceptor antagonist administration into the CeA may block SIH.Bilateral microinjections of drug or saline via chronically implanted CeA cannulae were followed by either a period of restraint stress or rest. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Intrathecal administration of α 2 -AR agonists induces antinociception in humans and animal models whereas the opposite occurs with α 2 -AR antagonists (Eisenach et al, 1996;Budai et al, 1998). However, NA may trigger pain facilitation after brain release (Bie et al, 2003;Ortiz et al, 2008;Martins et al, 2015). Further adding complexity to the studies of noradrenergic pain modulation, an effect of the pain model was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Intrathecal administration of α 2 -AR agonists induces antinociception in humans and animal models whereas the opposite occurs with α 2 -AR antagonists (Eisenach et al, 1996;Budai et al, 1998). However, NA may trigger pain facilitation after brain release (Bie et al, 2003;Ortiz et al, 2008;Martins et al, 2015). Further adding complexity to the studies of noradrenergic pain modulation, an effect of the pain model was reported.…”
Section: Introductionmentioning
confidence: 99%
“…15 α-2 Receptors are also located in the spinal cord dorsal horn 16 and in brain regions associated with pain modulation including the hypothalamus and amygdala. 1719 …”
Section: Introductionmentioning
confidence: 99%
“…More specifically, microinjection of the  2 adrenergic receptor agonist in the CeA decreased the sensitizing effect of foot shocks on the amplitude of the acoustic startle response [73]. Furthermore, microinjection of the noradrenergic agonists clonidine in the CeA increased the tail-flick latency, again supporting a role for noradrenergic receptors in antinociception [74], whereas microinjections of an  2 receptor antagonist preceding the induction of stress by restraining, blocked the stress-induced hypoalgesia as measured as the paw-withdrawal latency [14]. Together, these data are consistent with the involvement of the amygdala in stress-induced analgesia and hypoalgesia, triggered by stress-induced release of noradrenaline in this region.…”
Section: Analgesic and Hypoalgesic Neuromodulation By Noradrenalinementioning
confidence: 77%
“…However, over recent years, a role for the amygdala in hypoalgesia and analgesia during emotionally heightened states such as fear has become of more interest. Much evidence has implicated release of noradrenaline, and activation of the α 2 receptors in the central amygdala in stress-induced analgesia [14]. The parabrachial afferents form large perisomatic excitatory synapses in the central amygdala, and carry nociceptive information into the nociceptive amygdala [43] are key targets for modulation by noradrenaline [71].…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation